2019
DOI: 10.1002/srin.201900477
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Inclusion Formation in Light‐Weight Fe–Mn–Al Steels using Automated Scanning Electron Microscope Equipped with Energy‐Dispersive X‐Ray Spectroscopy

Abstract: Herein, the effect of Mn content on the characteristics and the formation of inclusions in light‐weight Fe–Mn–Al steels is investigated. Three laboratory‐produced steels, containing different manganese contents (2%, 5%, and 20%) are investigated. 2D and 3D inclusion characterization methods are used to establish inclusion classification rules for oxide, sulfide, and nitride inclusions using an automated scanning electron microscope (SEM) equipped with energy‐dispersive X‐ray spectroscopy (EDS) (ASPEX system). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…There has been thorough research on the microstructure and mechanical properties of AHSS [1][2][3][4][5][6][7][8], while knowledge related to non-metallic inclusions in AHSS is still limited. Previous studies [9][10][11][12][13][14][15] on non-metallic inclusions have identified the primary type of inclusions as MnS, Al 2 O 3 , and AlN. The presence of Al 2 O 3 -MnO is also reported.…”
Section: Introductionmentioning
confidence: 92%
“…There has been thorough research on the microstructure and mechanical properties of AHSS [1][2][3][4][5][6][7][8], while knowledge related to non-metallic inclusions in AHSS is still limited. Previous studies [9][10][11][12][13][14][15] on non-metallic inclusions have identified the primary type of inclusions as MnS, Al 2 O 3 , and AlN. The presence of Al 2 O 3 -MnO is also reported.…”
Section: Introductionmentioning
confidence: 92%
“…The 'Other' class contained complex oxide inclusions besides the aforementioned classes. The details of the inclusion classification were described elsewhere [14].…”
Section: Plate-like Angular Needle Agglomerate Irregularmentioning
confidence: 99%
“…The solid fraction (g s ) values at which AlN would start to form for the S1 compositions were calculated by adopting the Scheil equation [18,29,30]. The detailed procedure for this calculation was given elsewhere [14,18]. According to the estimates, the g s values for S1 samples should be higher than 0.11 (based on 10 ppm N), and they could be as high as 0.71 assuming 2 ppm N content.…”
Section: Thermodynamics Of Aln Formationmentioning
confidence: 99%
See 2 more Smart Citations